SURAT-SURAT NABI SAW KEPADA PARA RAJA NONMUSLIM: (STUDI KOMPARASI KITAB TARIKH, SIRAH DAN HADIS) - Syamsudin, Kinkin (Universum, 2023)
This article presents a comparison of various redactions of the letter of the Prophet Saw. that had been sent to nonmuslim kings. The studies discussed are the result of literature studies and are qualitative. Data on the letters of the Prophet Saw. collected from the book of tarikh, sirah and hadith. Once collected, the data is classified and analyzed descriptively. The results of the discussion concluded that; first, the eight letters that have been sent by the Prophet Saw. its history and editors are listed by many authors of the book of tarikh and sirah. While only a few of the authors of the hadith narrate it, even then with not very complete redactions. Secondly, despite having the same purpose, the letters that the Prophet Saw. once sent were basically written with different models and patterns between each letter.